EFFECT OF FEEDING MILK REPLACER ON GROWTH PERFORMANCE OF YAK CALVES - N.K. Sarma; M. Morang; J. Saharia (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An investigation was carried out on 18 numbers of new born Yak calves of both sexes to study the cost of raising the calves under three feeding systems. The calves were placed under three feeding systems: T1 - (natural suckling), T2- (milk replacer) and T3- (whole milk with bottle feeding like foster mother).  Each group had 3 male and 3 female calves. A milk replacer was prepared with the conventional feed ingredients containing 22.42 per cent CP and was offered as per recommendation of Arora (1979) on dairy calf. The calves under T1 were allowed to suckle ad lib mothers’ milk two times a day and calves under T3 were offered yak whole milk as per body weight requirement. During three months of experimental period, no significant body weight gain was observed in all three groups. Feed conversion efficiency was significantly higher in T2 group. The cost incurred on feed, fodder, concentrate mixture, milk and milk replacer were recorded to calculate the cost of raising calves under different treatments. The total cost of feeding of calves during the experiment period was Rs.7812.00, 6468.46 and 5884.00 for T1, T2 and T3 respectively. The cost of raising calves with milk replacer seems to be marginally higher than whole milk feeding.  It is concluded that the yak calves can be raised under milk replacer feeding from birth to three months of age without affecting the growth.